THE ROLE OF THE SOUTH AFRICAN NATIONAL DEFENCE FORCE IN POLICING - Montesh, Moses; Basdeo, Vinesh (Scientia Militaria - South African Journal of Military Studies, 2012)
The subjects of law enforcement, the protection of society and more specifically criminal justice practices have sparked lively debate in both public and legal spheres. Over the past decade, human right scholars/activists as well as civil society organisations in South Africa have advocated for the creation of new laws, policies and practices in relation to the fight against crime. Reflecting on over a decade of law enforcement, this article attempts to highlight some of South Africa’s unique experiences in the fight against crime as well as the specific discursive challenges faced by reformers in developing an appropriate contextual approach. This article reflects specifically on the often-overlooked role, which the South African National Defence Force (SANDF) can play in precipitating and sustaining law enforcement in civil society. It also further reflects on the legislative decisions made in this regard. The article also examines the general overview of shifts in policing policies and practices with regard to policing and law enforcement in the South African context.